2017
DOI: 10.17796/1053-4628-41.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Resin Restorative Materials by Streptococcus Mutans: A Pilot Study

Abstract: SM degrades the resin based restorative materials & among the tested materials Resin Modified GIC appears to be most Biostable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It has been reported that S. mutans contains esterases that can potentially degrade resin-based restorative materials [32]. Gautam et al [33] revealed by in vitro test that degradation by S. mutans was reduced for resin composites containing S-PRG filler (Beautifil II) compared with other commercial resin composites. On the other hand, Yoshihara et al [34] reported production of many holes on the surface of S-PRG filler-containing resin composites after immersion in lactic acid at pH 4.0 for 3 days, while no change in surface An investigation of demineralization in the tooth structure surrounding filling materials revealed that S-PRG filler-containing resin composites inhibited the demineralization of wall and outer lesions in enamel and dentin and increased the surrounding tooth hardness [30].…”
Section: Restorative Treatmentmentioning
confidence: 99%
“…It has been reported that S. mutans contains esterases that can potentially degrade resin-based restorative materials [32]. Gautam et al [33] revealed by in vitro test that degradation by S. mutans was reduced for resin composites containing S-PRG filler (Beautifil II) compared with other commercial resin composites. On the other hand, Yoshihara et al [34] reported production of many holes on the surface of S-PRG filler-containing resin composites after immersion in lactic acid at pH 4.0 for 3 days, while no change in surface An investigation of demineralization in the tooth structure surrounding filling materials revealed that S-PRG filler-containing resin composites inhibited the demineralization of wall and outer lesions in enamel and dentin and increased the surrounding tooth hardness [30].…”
Section: Restorative Treatmentmentioning
confidence: 99%
“…Higher biofilm growth indirectly increases the effectiveness of acid demineralization by both increasing acidity and reducing the diffusion of salivary buffering at the tooth interface 15 . Current evidence suggests that S. mutans has a multi‐factorial role in the destruction of the tooth‐resin composite interface since ester bond degradation can be pronounced during periods of higher pH (before and during early sucrose exposure) and tooth interfacial demineralization occurs during low pH, where bacterial esterases are less active 8,16 . A cycle of ester bond hydrolysis within the polymer and tooth demineralization may affect the mechanical integrity of both the tooth and resin polymers, thus affecting the overall interfacial adhesive properties 7 .…”
Section: Introductionmentioning
confidence: 99%
“…15 Current evidence suggests that S. mutans has a multi-factorial role in the destruction of the tooth-resin composite interface since ester bond degradation can be pronounced during periods of higher pH (before and during early sucrose exposure) and tooth interfacial demineralization occurs during low pH, where bacterial esterases are less active. 8,16 A cycle of ester bond hydrolysis within the polymer and tooth demineralization may affect the mechanical integrity of both the tooth and resin polymers, thus affecting the overall interfacial adhesive properties. 7 Bacterial degradation may contribute to the low (~65%)-clinical success rate of resin composites after 10 years in high caries risk patients.…”
mentioning
confidence: 99%
“…The surface of resin-based restorative materials can be negatively affected by bacterial biodegradation or by salivary enzymes, 1,2,3 and occlusal and toothbrushing induced wear. 4,5 Previous studies have shown that toothbrushing can increase the surface roughness and alter the surface topography of resin composites, 6,7 which can increase the formation of biofilm on the tooth.…”
Section: Introductionmentioning
confidence: 99%